Polarization, Hyperpartisanship and Echo Chambers: How the disinformation about Covid-19 circulates on Twitter - Recuero, Raquel (2020)
In this paper, we analyze the circulation of disinformative links about the Covid-19 pandemic on Twitter, using a dataset of 159,560 links collected using Twitter’s API between the months of March and July 2020. By mapping the network and observing the neighborhood of links and the most shared links, we observed a polarization and reduction of the circulation of links according to their direction (either pro hydroxychloroquine or anti hydroxychloroquine). The results also show more activity in the dissemination of pro hydroxychloroquine links, a group where we could also find more disinformation and more hyperpartisan media. Likewise, the circulation of traditional and institutional media is quite reduced in this group, strengthening the association between hyperpartisan media and disinformation.